Pengaruh PDRB, dana perimbangan, dan investasi terhadap belanja modal di Provinsi Sumatera Utara Tahun 2017-2019 - Nisa Batu Bara, Khairun; Nelsari Malau, Yois; Novita Sirait, Diana; Marijun Sianturi, Elisabet (Jurnal Paradigma Ekonomika, 2022)
This study aims to determine the effect of GRDP, Balancing Fund, and Investment on Special Capital Expenditures in North Sumatra Province in 2017-2019. This study uses a quantitative presentation type. The number of samples was 33 districts/cities. The sample selection was made using the saturated sampling method. And the data is retrieved through the website www.bpssumut.go.id. Hypothesis testing data is tested using classical assumptions. The adjusted R square value is 0.633, meaning 63.3%, and other independent variables of 36.7%. The results of the discussion state separately that the PDRB, Balancing Funds have an influence, but Investment does not affect Capital Expenditures. GRDP, Balanced Fund, and Investment have an impact on capital expenditure